Strategic International Partnerships: Global North and Global South Discourses - Lumb, Punita (Comparative and International Education / Éducation comparée et internationale, 2023)
This paper explores how international partnerships are conceptualized between core Anglophone, European, and African universities. Internationalization strategies are examined from a decolonial lens to situate the findings within a global context that is entangled in the consequences of colonialism and ongoing coloniality that continue to perpetuate global inequities, including devaluing of Indigenous and local knowledge. Findings suggest that institutions in the Global North still view Africa, and the Global South in general, from a deficit lens and in need of aid, knowledge, and direction. Strategies from the Global North use terms like “mentoring,” “development” and “poverty reduction” when describing their partnerships in the Global South. In contrast, institutions from Africa highlight their desire to be knowledge producers and contribute to research excellence on a global level. Furthermore, institutions in all regions frame strategic international partnerships as those that will boost their reputation or image as they engage in a race for status and global rankings; however, strategies do not describe how they will approach such partnerships in a very uneven global playing field between the Global North and Global South. Finally, the Global South continues to be viewed as a source of international students and as such, partnerships pursued in Africa and the Global South by core Anglo and European institutions focus on recruitment of students as one of the rationales or benefits of partnerships. Given these findings, international strategies for Global North-South partnerships continue to reproduce colonial hierarchies of power, preventing more equitable approaches to partnerships.